Magnetic properties of a hexagonal nanowire system with mixed spin: Application of the stochastic Glauber dynamics with mean-field approximation. (November 2022) - Mendes, R.G.B.; Santos, J.P.; Sá Barreto, F.C.
Abstract: The Glauber stochastic dynamics with mean-field approximation has been applied to study the magnetic behavior of a mixed spin nanowire structure. Considering a hexagonal symmetry of the distribution of the sites, the whole lattice was interpreted as composed of two sub-lattices, a midland chain of spin-1/2 and an outer shell hexagonal of spin-1. Through the curves of the Lyapunov exponent and of the order parameters, the magnetic phase diagrams were plotted relating the magnitude of the external magnetic field with the temperature, T, h o D . For negative values of the anisotropic constant D the system showed more than one temperature of phase transition for a same magnitude of external magnetic field. This split of the phase transition branch was understood as a phase transition decoupling of the two sub-lattices. The reason for this phase transition decoupling is a competition between the states S = ± 1 and S = 0 just in one of the sub-lattices. This behavior had not been observed in the absence of an oscillating magnetic field. Highlights: Glauber dynamic theory applied to magnetism in low-dimensional structure. Mixed spin hexagonal nanowire lattice. Magnetic order in low-dimensional structure. The observation of a phase transition decoupling between two different sub-lattices.